Peningkatan Hasil Belajar Fisika Melalui Model Pembelajaran Kooperatif Tipe Team Assisted Individualization pada Siswa Kelas VII.D SMP Negeri 2 Bangkala Kabupaten Jeneponto - Suhardi Suhardi; Satriani Hanaping; Muhammad Amin Said (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
Abstract This research is a class action (Classroom Action Research), which aims to improve learning outcomes Physics VII.D grade students of SMP Negeri 2 Bangkala through Cooperative Learning Model Team Assisted Individualization. The subjects were VII.D grade students of SMP Negeri 2 Bangkala on odd semester 2013/2014 academic year consisting of 36 students. Research conducted two cycles consisting of four activities, namely: planning, action, observation and reflection. In the first cycle was conducted over four sessions and the second cycle was conducted over four sessions. Data collection was done by studying the results of the final tests of learning at the end of the first cycle and the end of the second cycle. The collected data were analyzed quantitatively and qualitatively. The results of the quantitative analysis of physics learning outcome data indicate that the number of students classified as learning completed the first cycle were completed only 22 0rang 61.11% and in the second cycle up to 25 people who completed 69.44%. The results of the qualitative analysis showed an increase in activity of students during the learning process through a model of Cooperative Learning Physics Team Assisted Individualization type. Based on these results it can be concluded that the physics learning through cooperative learning model of Type Team Assisted Individualization can improve student learning outcomes. Keywords: Results Learning, Cooperative Learning Model Team Assisted Individualization, Qualitative, and Student Activities Abstrak Penelitian ini adalah penelitian tindakan kelas (Classroom Action Research) yang bertujuan meningkatkan hasil belajar Fisika siswa kelas VII.D SMP Negeri 2 Bangkala melalui Model Pembelajaran Kooperatif Tipe Team Assisted Individualization. Subjek penelitian ini adalah siswa kelas VII.D SMP Negeri 2 Bangkala pada semester ganjil tahun pelajaran 2013/2014 yang terdiri dari 36 siswa. Penelitian dilaksanakan dua siklus yang terdiri dari empat kegiatan, yaitu: perencanaan, pelaksanaan tindakan, observasi dan refleksi. Pada siklus I dilaksanakan selama empat kali pertemuan dan pada siklus II dilaksanakan selama empat kali pertemuan. Pengumpulan data hasil belajar dilakukan dengan tes akhir belajar pada akhir siklus I dan akhir siklus II. Data yang terkumpul dianalisis secara kuantitatif dan kualitatif. Hasil analisis kuantitatif data hasil belajar fisika menunjukkan bahwa jumlah siswa yang tergolong tuntas belajarnya pada siklus I hanya 22 0rang yang tuntas 61,11% dan pada siklus II mencapai 25 orang yang tuntas 69,44%. Hasil analisis kualitatif menunjukkan terjadinya peningkatan aktivitas siswa selama proses pembelajaran Fisika melalui model pembelajaran Kooperatif Tipe Team Assisted Individualization. Berdasarkan hasil penelitian ini dapat disimpulkan bahwa pembelajaran Fisika melalui model Pembelajaran Kooperatif Tipe Team Assisted Individualization dapat meningkatkan hasil belajar siswa. Kata-kata Kunci: Hasil Belajar, Model Pembelajaran Kooperatif Tipe Team Assisted Individualization, Kualitatif, dan Aktivitas Siswa